Influence of isobutyric acid supplementation on nutrient intake, its utilization and growth performance of crossbred calves fed low protein and urea containing rations - MISRA, A. K; THAKUR, S S (The Indian Journal of Animal Sciences, 2014)
The present experiment was conducted to observe the beneficial effect of dietary supplementation of sodium salt of isobutyric acid in low protein and urea containing wheat straw (WS) based diets. Eighteen crossbred growing calves, divided into 3 similar groups, were fed a basal diet consisting of wheat straw, concentrate mixture and green oat fodder in 40:40:20 proportion (T1), basal diet + isobutyric acid (BCFA) @0.75% of basal diet (T2) and basal diet +BCFA+ Urea to replace 1/3rd of dietary nitrogen (T3) for 120 days. The average DMI (kg/100kg BW) was higher in T3 (2.55) as compared to Tr (1.95) and T2 (1.95). The dietary supplementation of isobutyric acid improved the DM, OM and CF digestibilities by 8.6, 8.0 and 13.2% over T1. The DCP content of experimental rations was similar in all the groups. However, the DCP intake (g/day and g/kg W0.75) was higher in T3 (304.55 and 6.70) as compared to T1 (217.90 and 5.01) and T2 (226.94 and 5.52). Similarly TDN intake (g/day and g/kg W0.75) was also higher (P